ebi regulates epidermal growth factor receptor signaling pathways in Drosophila. - Dong, X.; Tsuda, L.; Zavitz, K.H.; Lin, M.; Li, S.; Carthew, R.W.; Zipursky, S.L. (Genes & Development, 1999)
ebi regulates the epidermal growth factor receptor (EGFR) signaling pathway at multiple steps in Drosophila development. Mutations in ebi and Egfr lead to similar phenotypes and show genetic interactions. However, ebi does not show genetic interactions with other RTKs (e.g., torso) or with components of the canonical Ras/MAP kinase pathway. ebi encodes an evolutionarily conserved protein with a unique amino terminus, distantly related to F-box sequences, and six tandemly arranged carboxy-terminal WD40 repeats. The existence of closely related proteins in yeast, plants, and humans suggests that ebi functions in a highly conserved biochemical pathway. Proteins with related structures regulate protein degradation. Similarly, in the developing eye, ebi promotes EGFR-dependent down-regulation of Tramtrack88, an antagonist of neuronal development.